Basic ionic liquid [BMIM][OH] as heterogeneous catalyst mediated solvent-free Stobbe condensation applying grindstone technique for the synthesis of novel β-arylidene-β-benzoylpropionic acid derivatives. Issue 2 (3rd April 2017) - Lambat, Trimurti L.; Deo, Sujata S.
ABSTRACT: The basic ionic liquid 1-butyl-3-methylimidazolium hydroxide, i.e. [BMIM][OH], proficiently catalyzed Stobbe condensation in solvent-free condition. An extensive range of aromatic aldehydes simply undergo condensations with methyl-β-benzoyl propionate. The reactions proceed at room temperature and are very fast (10 min). However, the most crucial feature of this methodology is the solvent-free approach and applying grindstone technique for condensation, which is generally not possible by any other conventional reagents and was not addressed adequately in literature providing a general and convenient procedure. The potential application of [BMIM][OH] in organic synthesis is increasing rapidly due to its high yields of the desired products (80%–92%), minimal reaction time, reaction simplicity, and low-cost chemicals. All novel compounds of β-arylidene-β-benzoylpropionic acid derivatives were characterized by IR, 1 H NMR, and mass spectra. Abstract :